2016
DOI: 10.4236/psych.2016.713163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Support on Athletes’ Psychological Well-Being: The Correlations among Received Support, Perceived Support, and Personality

Abstract: The current study aimed to examine the impact of received support and perceived support on athletes' psychological well-being. Furthermore, correlations between received support, perceived support, and personality were investigated. Two hundred and thirty-nine Japanese university student athletes (M age = 19.69 ± 1.01 years) completed the questionnaires regarding social support, psychological well-being, and personality. The results indicated that received support was positively correlated with athletes' psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Some similar studies in the sport context have also confirmed that social support is an effective buffer between adverse sports events and negative responses (for instance, when competition was lost) and is associated with injured athletes' well-being (Bianco and Eklund, 2001; Lu and Hsu, 2013; Rees and Hardy, 2000). The study by Katagami and Tsuchiya (2016) highlighted that perceived social support positively correlated with positive athletes‘ self-schema and the receipt of social support may be a key factor in athletes’ psychological well-being not only for sport performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some similar studies in the sport context have also confirmed that social support is an effective buffer between adverse sports events and negative responses (for instance, when competition was lost) and is associated with injured athletes' well-being (Bianco and Eklund, 2001; Lu and Hsu, 2013; Rees and Hardy, 2000). The study by Katagami and Tsuchiya (2016) highlighted that perceived social support positively correlated with positive athletes‘ self-schema and the receipt of social support may be a key factor in athletes’ psychological well-being not only for sport performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Gurung (2013) held that the main components of social support included received support, enacted support, and perceived availability of support. In contrast from perceived social support which represents one’s appraisal of available social support, received support mainly described the substantial or actual support a person received (Helgeson,1993; Katagami & Tsuchiya, 2016). Social network generally defines the sources of support, and thus is also considered as an important indicator of social support.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies confirmed coaches are among the most critical sources of support for athletes, considering the regularity and patterns of interaction, guidance and expertise they provide on an almost daily basis to young athletes. 5,8,31 In the present study, this is especially true in a university setting where trainings and competitions are structured, governed by concrete rules and policies, and the dyadic relationship is bound to certain goals, targets and outcomes in a concrete way. Our results may help in creating an implementation framework of social support that emphasizes key strategies for coaches and practitioners to integrate in their approaches in sport coaching.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Chan [30] reported that Taiwanese college athlete's perceived social support from their parents, friends, and significant others were linked to their career choices and beliefs about their capacity to make career-related decisions. Furthermore, collegiate student athletes in Japanese perceived social support closely linked to positive self-schema [31], and the amount of social support provided to the teammates [32]. However, despite these recent positive findings on the importance of providing social support to athletes in some Asian countries, there is a need for a better understanding of the implementation strategies relevant to the social support process provided by competitive sport coaches at the university level, as opposed to school or college-based coaches who have previously been studied to a greater extent [e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation